Mechanical cooperation between time-dependent and covalent bonds in molecular damage of polymer networks - Zachary T. White; Aidan M. Smith; Franck J. Vernerey (Communications Physics)
Abstract Most covalent polymer networks inherently contain a population of dynamic bonds, such as entanglements and physical associations, that interact with permanent cross-linked chains. This interaction plays a critical role in the mechanical behavior of the material and is evident from experimental observations. However, understanding the underlying nature and mechanisms of this coupling remains a significant challenge. To address this shortcoming, we develop a coarse-grained numerical model that incorporates time-dependent dynamic bonds and permanent covalent bonds. We investigate the effect of temperature, through modification of dynamic bonds intrinsic dissociation rate, and percolation on the mechanical interplay of hybrid networks. We show that high network connectivity constrains the microscopic deformation of local chains ensuring affine deformation, shielding the permanent network from early damage accumulation in the process. Conversely, the gradual erosion of dynamic bonds leads to highly inhomogeneous redistribution of stress and the emergence of structural heterogeneities. Finally, we investigate networks fracture behavior with a single-edge notch defect under varying temperature and network percolation. We demonstrate that the introduction of dynamic bonds explains delocalization of damage from the fracture plane, increasing energy dissipated through bond rupture. This shift can be understood in terms of an increase to the damage zone, where the opening of large-scale heterogeneities leads to an inhomogeneous redistribution of stress from the fracture interface to the bulk.